Experimental study on the effect of filler size on the denitrification of SBBR process in low temperature. Issue 4 (August 2019) - Bian, Dejun; Yan, Yiming; Wu, Ji; Ai, Shengshu; Wang, Fan; Nie, Zebing
Abstract: In order to study the effect of filler size on the treatment of low temperature wastewater by SBBR process, three groups of SBBR reactors were established. They used cubic sponges with side lengths of 1, 1.5 and 2cm as filling fillers, respectively. The denitrification effect of the three fillers was compared under the conditions of stable water temperature of (10±1)°C, HRT of 10h and reactor filling rate of 16%. The results showed that the removal of NH4 + -N and TN in the reactor with the filling size of 1cm was the best, and the removal rates were 96% and 80%. The NH4 + -N and TN removal rates of the reactors filled with the other two sizes of fillers were all below 80% and 70%. The membrane biomass measurement of the reactor showed that the smaller size of the filler has a larger specific surface area, which was beneficial to mass transfer and microbial growth and enrichment, thereby promoting the denitrification of low temperature wastewater.